Assessment of Levels of Selected Heavy Metals in Borehole Water in Zuru Metropolis, Kebbi State Nigeria - Adamu Zubairu Utono; Usman Rufai Fakai; Aliyu Garba; Basiru Muhammad Suru (MultiTech Publisher, 2023)
This paper assesses certain heavy metal concentrations in borehole water within Zuru Metropolis, Kebbi State. Utilizing rigorous sampling and analytical methods, the study aims to provide insights into the potential health risks associated with heavy metal exposure in the local water supply. Twenty different borehole water samples were assessed for Zn, Pb, Hg, Mn, Cr and Cd levels (mg/l). The results revealed that only few boreholes water samples had concentration levels of heavy metals that are not within WHO recommended levels. While chromium and cadmium levels are below detection limits .The findings contribute to the understanding of water quality in the region, offering valuable information for public health interventions and water management strategies.